Complications of labial minor salivary gland biopsy and comparison of complications in patients with and without primary Sjögren's syndrome - Ayar, Koray; Doğan, Ali; Küçük, Adem; Tunç, Recep (The European Research Journal, 2020)
Objectives: Labial minor salivary gland biopsy (MSGB) is a procedure in which complications such as bleeding, hematoma, numbness, wetness can be seen after the procedure. It is not known whether these complications have changed in patients with primary Sjögren's syndrome (PSS). The aim of this study is to investigate the frequency of complications after the labial MSGB and to investigate whether these complications has changed in PSS. Methods: Participants with a preliminary diagnosis of PSS who underwent a labial MSGB without any suture were included in the study. One month after the procedure, the complication screening questionnaire was administered face-to-face interview or by telephone. All complications were compared between PSS and non-PPS groups. Results: Complications screening questionnaire was applied to 99 participants (face to face with 79 participants and by telephone with 20 participants). After the procedure, 17.2% of the participants had uncomfortable bleeding, 2.0% had persistent numbness which continues more than 1 week and 1.0% had wetness and hematoma. Bleeding duration was more than 1 hour in 11.1% of the participants. Complications were not different between PSS and non-PSS groups (p > 0.05). Conclusions: After the labial MSGB procedure without suturing, uncomfortable bleeding is frequent and the duration of bleeding is long, but complications other than bleeding are rare. The incidence of complications after labial MSGB procedure was not different in participants with PSS than in those without PSS.